2003
DOI: 10.1128/aem.69.9.5328-5335.2003
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Activated Cell Sorting of Specific Affibody-Displaying Staphylococci

Abstract: Efficient enrichment of staphylococcal cells displaying specific heterologous affinity ligands on their cell surfaces was demonstrated by using fluorescence-activated cell sorting. Using bacterial surface display of peptide or protein libraries for the purpose of combinatorial protein engineering has previously been investigated by using gram-negative bacteria. Here, the potential for using a gram-positive bacterium was evaluated by employing the well-established surface expression system for Staphylococcus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
(61 reference statements)
1
17
0
Order By: Relevance
“…The extracted cell wall proteins were purified on HSA columns and analyzed using SDS–PAGE under reducing conditions (Fig. 2) [14]. The three mutant Z fusion proteins all migrated as full‐length proteins with a similar molecular weight as the previously characterized Z wt fusion protein (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The extracted cell wall proteins were purified on HSA columns and analyzed using SDS–PAGE under reducing conditions (Fig. 2) [14]. The three mutant Z fusion proteins all migrated as full‐length proteins with a similar molecular weight as the previously characterized Z wt fusion protein (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…It was demonstrated that cells expressing the ligand binding affibody could be enriched almost quantitatively from a moderate excess of non‐ligand binding cells by a single round of FACS. Extending the method to include two rounds of selection with reamplification by growth after the first round, target cells could be enriched 25,000‐fold from a model system consisting of one target cell in a million [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface display plasmid vector, pSCX:Z wt (Wernérus et al ., 2003), was used for construction of the new vectors. The vector pSCX:Z wt His 6 3C, hereafter denoted pHis3C, was created by ligating a sticky‐end fragment of annealed oligonucleotides, encoding the peptide H6EALFQGP, downstream of the Z wt domain in the vector pSCX:Z wt digested previously with SalI and HindIII restriction enzymes (Fermentas, Vilnius, Lithuania).…”
Section: Methodsmentioning
confidence: 99%
“…The successful applications of yeast and E. coli display in combinatorial protein engineering in the early 2000, and the potential of cell‐based systems to become attractive alternatives to phage display, inspired the evaluation of staphylococcal cell‐surface display also for this purpose. Employing a second‐generation display vector, the staphylococcal system was evaluated in a model library application using flow cytometry . The system was further optimized by the introduction of a surface expression normalization strategy using the ABP‐tag and fluorescently labeled albumin in order to improve the ability of discriminating between closely related binders …”
Section: Selection Systemsmentioning
confidence: 99%